Web-Based And Whatsapp Gateway Tuition Payment Information System (Case Study Of SMK Antartika 2 Sidoarjo): Sistem Informasi Pembayaran SPP Berbasis Web Dan WA Gateway (Studi Kasus : SMK Antartika 2 Sidoarjo) - Imanda, Almyra Gitta; Eviyanti, Ade; Hindarto, Hindarto; Setiawan, Hamzah (Universitas Muhammadiyah Sidoarjo, 2023)
The tuition paymant system at Vocational High School Antartika 2 Sidoarjo is still carried out semi- manually, meaning that transactions are already using a computer but data recaps are still recorded in books manually. This can slow down the payment process causing some problems. The method used is an object-oriented method using the Unified Modeling Language (UML). While the data collection techniques used are by way of observation, interviews, and documentation. This journal will discuss the design of a web-based tuition paymant information system and Whatsapp gateway using Whatsapp messages to be sent to each student's guardian. This plan aims to facilitate the administration of the finance department in recording tuition paymant data and making reports, as well as making it easier for students' parents to provide payment information via Whatsapp messages. The author hopes that with this application planning it is hoped that it will run more effectively and efficiently both in conducting tuition paymant transactions, as well as in making reports so that it can help the school and parents of students also easily get information on tuition payments.